Pelatihan Instalasi Listrik Dasar Sebagai Upaya Peningkatan Keselamatan dan Kemandirian Ibu-Ibu PKK Dusun IV Desa Muarajalai - Adi Febrianton; Romiyadi Romiyadi; Indah Purnama Putri; Widya Sinta Mustika; Purnama Irwan; Yudi Dwianda (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
Electrical energy is a primary source of energy in daily life, with various electrical devices supporting human activities. Sometimes, electrical equipment experiences damage, with repair risks ranging from small to large scale. For damage with medium to large-scale risks, specialized experts are usually needed for repairs. However, damage to electrical installations with small-scale risks should be manageable by household members, especially housewives. Many housewives are afraid and do not understand how to handle electrical issues, even though they are active at home every day. Therefore, there is a need for training and counseling on simple electrical installations so that they can handle it confidently and safely. One form of training that can be provided is the creation of an electrical outlet set for PKK mothers in Muarajalai Village, Hamlet IV. This training aims to equip the PKK mothers with the skills and knowledge about tool specifications, tool functions, and safety procedures when using electrical equipment. With this training, it is hoped that they will be able to maintain and repair simple electrical installations at home without relying on experts, while also increasing their confidence and independence in handling everyday electrical problems.